Rational designed Fe-ZIFs@CoP nanoplatforms for photothermal-enhanced ROS-mediated tumor therapy - Wang, Chen; Ning, Shufang; Mai, Jinling; Zhao, Shanyu; Jiang, Wenwei; Pan, Junjie; Wu, Feifei; Liu, Qiuju; Zhang, Qinle (Frontiers in Bioengineering and Biotechnology, 2024)
Metal-organic frameworks (MOFs), with biocompatible and bio-friendly properties, exhibit intriguing potential for the drug delivery system and imaging-guided synergistic cancer theranostics. Even though tremendous attention has been attracted on MOFs-based therapeutics, which play a crucial role in therapeutic drugs, gene, and biomedical agents delivery of cancer therapy, they are often explored as simple nanocarriers without further "intelligent" functions. Herein, Fe-doped MOFs with CoP nanoparticles loading were rationally designed and synthesized for photothermal enhanced reactive oxygen species (ROS)-mediated treatment. Fe-ZIFs@CoP could generate efficient ROS through the Fenton reaction while depleting glutathione for amplifying oxidative stress. Particularly, due to the photothermal effect of Fe-ZIFs@CoP, the hyperthermia generated by as-synthesized Fe-ZIFs@CoP facilitated the advanced performance of the Fenton effect for a high amount of ROS generation. The promising "all-in-one" synergistic MOFs platform herein reported provides some prospects for future directions in this area.